Strategi Pemasaran Dalam Upaya Meningkatkan Pelayanan Jasa Pada PT AeroJasa Kargo Tahun 2021 - Etgar Ramadhani Pambudi; Mustikasari Mustikasari; Siti Nurhayati; Sarinah Sihombing (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
PT Aerojasa Cargo is one of the subsidiaries in the business strategy group of the Garuda Indonesia Group Aerowisata unit which is engaged in transportation, tourism, hospitality, logistics and flight catering services. Tbk. The method used in this research is descriptive qualitative using SWOT analysis. Based on the results of the SWOT analysis, the IFE matrix shows that the strength and weakness factors have a total score of 3.47. This indicates that the condition is in a very strong internal position. Furthermore, the EFE matrix shows that the opportunity and threat factors have a total score of 3.14. This indicates that the Cargo Services business can respond to the opportunities that exist in the right way so as to avoid threats in the industrial market. The quadrant diagram shows that PT Aero Jasa Cargo is in the Growth quadrant where the quadrant is in a very favorable condition. The results of the SO strategy, obtained the strength factor that must be maintained in order to be able to take the existing opportunities, the ST strategy shows that the company must maximize the strength to overcome the existing threats, the WO strategy, take advantage of the existing opportunities by minimizing the company's weaknesses. As well as the WT strategy which requires companies to be able to minimize weaknesses and avoid threats.